2012
DOI: 10.1371/journal.pone.0050195
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Formyl Peptide Receptor 1 (FPR1) Gene in Primary Human Macrophages

Abstract: The formyl peptide receptor 1 (FPR1) is mainly expressed by mammalian phagocytic leukocytes and plays a role in chemotaxis, killing of microorganisms through phagocytosis, and the generation of reactive oxygen species. A large number of ligands have been identified triggering FPR1 including formylated and non-formylated peptides of microbial and endogenous origin. While the expression of FPR1 in neutrophils has been investigated intensively, knowledge on the regulation of FPR1 expression in polarized macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…This is in line with the IL-4-mediated reduction in cell-surface expression for both receptors (Fig. 2D) (30). Repolarization of primary human macrophages with 10 nM RvE1 reduced but not totally ablated migration toward chemerin and did not influence migration toward fMLF.…”
Section: Rve1 Repolarized Human M1 Macrophages Migrate Less Toward Chsupporting
confidence: 84%
See 2 more Smart Citations
“…This is in line with the IL-4-mediated reduction in cell-surface expression for both receptors (Fig. 2D) (30). Repolarization of primary human macrophages with 10 nM RvE1 reduced but not totally ablated migration toward chemerin and did not influence migration toward fMLF.…”
Section: Rve1 Repolarized Human M1 Macrophages Migrate Less Toward Chsupporting
confidence: 84%
“…To investigate whether RvE1 causes a repolarization of inflammatory M1 macrophages, we sequentially stimulated primary human macrophages with LPS followed by the stimulation with RvE1, and characterized the polarization phenotype of these macrophages. As expected, LPS-stimulated M1 macrophages exhibited an increased transcription of IL-1b, TNF-a, and cell-surface expression of CD80 and CD206 (mannose receptor) (30,35), which returned to levels comparable with untreated macrophages upon removal of the stimulus for 4 d (data not shown). Sequential stimulation of these M1 macrophages with 10 nM RvE1 at day 1 of the 4-d incubation did not alter transcription for IL-1b and TNF-a, or cell-surface expression for ChemR23 and CD206 (Fig.…”
Section: Rve1 Repolarizes Human M1 Macrophagessupporting
confidence: 78%
See 1 more Smart Citation
“…When searching for such a chemotactic receptor that can promote phagocytosis as well, we focused on FPR1, which has been reported to be a non-classical chemokine receptor highly expressed on stimulated macrophages that also regulates phagocytosis. 22,23 To test our hypothesis, we overexpressed FPR1 on the HEK293 cells and observed the effects of FAM19A4 on the cells. The chemotaxis assays showed that FAM19A4 was able to recruit FPR1-expressing HEK293 cells in a dose-dependent manner (Figure 4a).…”
Section: Fpr1 Is a Functional Receptor Of Fam19a4mentioning
confidence: 99%
“…In addition, FPR1 is thought to play a role in sensing the endogenous signals of dysfunctional cells, which should attract leukocytes to the sites of inflammation and tissue damage. 11,22,23,25,26 As the ligand with the highest affinity for FPR1, fMLF has a Kd of 0.04 nM. 27 According to the ratio of Ki for fMLF (Ki50.08139 pM) and FAM19A4 (Ki558.81 pM) from the competition binding analysis, the Kd of FAM19A4 is 722 times that of fMLF.…”
Section: Fpr1 Is a Functional Receptor Of Fam19a4mentioning
confidence: 99%